DATA GOVERNANCE MECHANISMS IN INDONESIA’S COVID-19 DATA INTEGRATION SYSTEM - Nafi'ah, Binti azizatun (Sosiohumaniora, 2021)
During a pandemic, policy decisions are made quickly and correctly. The need for COVID-19 data becomes an absolute basis for policymaking. This paper focuses on the mechanism of COVID-19 data management in the national COVID-19  task forces to be able to provide valid and realtime data. Researchers used qualitative analysis, with primary and secondary data collection. Researchers interview 3 information from the ministry of communication and informatics as a public communication team in the task force to accelerate the handling of COVID-19. The results showed that even data management was based on structural, procedural, and relational mechanisms. Structure mechanism has been formed strongly through the task force team from the national to the regions. Procedural data mechanisms, although changing procedures are now at the point of data integration. The relation mechanism shows that the coordination and communication relationship between member task forces has been done quite well where coordination is always done quickly.